1991
DOI: 10.1007/bf00003698
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of algae and nutrient removal in a waste heat utilization process

Abstract: A process providing a beneficial use for waste heat and excess nutrients in the cooling waters of nuclear reactors and fossil-fueled power generating plants has been developed. The process involves the cultivation of selected strains of thermotolerant microalgae in heated discharge waters and the subsequent harvesting of the algal biomass for nutrient removal, recovery of energy and fertilizer, and extraction of high value products. The design of such a process is presented for a large cooling reservoir receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…It is of interest to determine not only the permissible (maximum, minimum, optimum) growth temperatures, but also the ability of specific strains to tolerate extremes that do not allow growth. Although the present study was inspired by a need to determine such limits as part of the development of an algal cultivation process (Wilde et al, 1991), the data may be of broader physiological and ecological interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest to determine not only the permissible (maximum, minimum, optimum) growth temperatures, but also the ability of specific strains to tolerate extremes that do not allow growth. Although the present study was inspired by a need to determine such limits as part of the development of an algal cultivation process (Wilde et al, 1991), the data may be of broader physiological and ecological interest.…”
Section: Discussionmentioning
confidence: 99%
“…A conceptual process to mitigate such combined thermal/nutrient impacts was recently described by Wilde et al (1991). It involves the use of the thermal effluents to cultivate filamentous, thermotolerant cyanobacteria, followed by harvesting of the cyanobacterial biomass to remove the nutrients responsible for eutrophication.…”
Section: Introductionmentioning
confidence: 99%
“…Although nature currently mitigates about half of current anthropogenic net C02 emissions, through absorption into oceans and storage in forests, the future of these natural processes is uncertain, and they may fail us when we most need them during the next century, when the expected, unavoidable, increased fossil fuel utilization will greatly increase the risks of major adverse impacts. And, it should be further recognized that even a modest reduction in C02 greatly reduces the risks of adverse climatic impacts (see discussion in Benemann, 1991). All these arguments point to the need for initiating risk reduction now, using the least expensive options (energy conservation, preservation of C in the biota) while developing other mitigation technologies for the long-term.…”
mentioning
confidence: 99%
“…Studies examining the effects of temperature on microalgae production in outdoor cultivation systems demonstrated that heated pond systems performed better (with higher growth yields) than unheated systems (up to strain specific maximum temperatures) . Higher temperatures generally increase microalgal growth rates and extend their growing season in temperate and cold climates, such as in Canada . As such, microalgal cultivation using waste heat from the cooling waters of fossil fuel powered electricity‐generating plants could be beneficial.…”
Section: Waste Streams For Microalgal Cultivationmentioning
confidence: 99%